Direct Current Processing in DC Motor Using Arduino and Peak Value Method - Ma'arif, Alfian; Sari, Nurjanah Arvika; Prasetya, Wahyu Latri; Feter, Muslih Rayullan; Saputra, Dodi; Setiawan, Muhammad Haryo (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
The research proposes about monitoring current of Direct Current (DC) Motor using microcontroller, current sensor and peak value method. The device is Arduino Uno R3 microcontroller, current sensor INA 219, motor driver L298, DC motor JGA25-370 and computer. The algorithm detects the inrush of the DC Motor Current. In the experiment result, the device can measurement the current sensor by varying the Pulse Width Modulation (PWM) such as 50-150. The method can avoid the zero current value. Thus, the proposed method could be implemented for monitoring the direct current of DC Motor.